2018
DOI: 10.1002/slct.201801649
|View full text |Cite
|
Sign up to set email alerts
|

Micron‐size Silicon Monoxide Asymmetric Membranes for Highly Stable Lithium Ion Battery Anode

Abstract: To meet the increasing demand for high energy density lithium ion batteries for electric vehicles and mobile electronics, it is mandatory to make revolutionary changes in electrode materials and chemistry. In this report, micron-size silicon monoxide powders are utilized to fabricate asymmetric membranes via a phase inversion method. We investigate the effects of carbonization temperature, silicon monoxide concentration and glues on membrane microstructure and electrochemical performance. It iss also observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Accordingly, the reaction mechanism of SiO to storage Li + ions is generally premised to include reversible and irreversible parts. [ 55,56 ] The irreversible reaction is usually written as follows: [ 55,56 ] SiO+2Li++2normale1Li2O+Si SiO+4Li++4normale1Li4SiO4+3Si …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the reaction mechanism of SiO to storage Li + ions is generally premised to include reversible and irreversible parts. [ 55,56 ] The irreversible reaction is usually written as follows: [ 55,56 ] SiO+2Li++2normale1Li2O+Si SiO+4Li++4normale1Li4SiO4+3Si …”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the reversible reaction is generally expressed as follows: [ 55,56 ] Si+xLi++xnormale1 LixSi 5SiO+2Li++2normale1 Li2Si2normalO5+3Si …”
Section: Resultsmentioning
confidence: 99%
“…Recently, Li's group proposed asymmetric membranes containing SiO micron-sized powders and carboxymethyl glue, which demonstrated 99.82% CE and >95% capacity retention after 110 cycles at a current density of 400 mA g −1 . 27 Nonetheless, these lab-scale techniques usually require tedious processing steps and are thus not easy to be scaled up. Moreover, the half-cell evaluations are mostly targeted to optimize several key performance metrics, that is, gravimetric capacity, rate behavior, or cycle life, at the penalty of fully discharged compaction density or areal mass loading, which are also indispensable in the full-battery assessment and cannot be omitted.…”
Section: Introductionmentioning
confidence: 89%
“…Therefore, tremendous effort has been made to explore the fundamental basics of high-capacity and high-energy electrode materials and many strategies have been proposed to conquer the obstacles of boosting energy density of the batteries. One strategy is to reduce particle size to nanoscale to alleviate mechanical strain. For example, Liu et al found that, during the first lithiation process, the nanoparticles with diameters less than 150 nm undergo volume expansion without fracturing or cracking, suggesting that nanoparticles can tolerate huge volume change .…”
Section: Corn-mediated Carbonaceous Host Matrixes For High-capacity E...mentioning
confidence: 99%